Association of Helicobacter pylori with Serum HIF-1α, HIF-2α, and Human Transmembrane Prolyl 4-Hydroxylase Activity in Patients with Chronic Gastritis - Sefa Ergün; Fadime Kutluk; Basar Can Turgut; Seyma Dumur; Uğurcan Sayılı; Dilek Duzgun Ergun; Hafize Uzun (Medicina)
Background and Objectives: Chronic mucosal infection with Helicobacter pylori (H. pylori) plays a key role in the development of gastroduodenal disorders such as chronic gastritis, peptic ulcers, gastric lymphoma, and gastric cancer by triggering local immune responses and inducing hypoxic and inflammatory conditions in the gastric mucosa. This study aims to evaluate the potential diagnostic value of hypoxia-inducible factors HIF-1α and HIF-2α, along with transmembrane prolyl 4-hydroxylase (P4H-TM), as biomarkers in H. pylori-positive patients. Additionally, the study investigates the association between these markers and alterations in lipid profiles, as well as their involvement in the molecular mechanisms underlying gastric conditions like gastritis, particularly in the context of H. pylori infection. Materials and Methods: This study was conducted at Istanbul Avcılar Murat Kölük State Hospital’s General Surgery Outpatient Clinic. A total of 60 participants were included: 40 patients diagnosed with chronic gastritis (20 H. pylori-positive and 20 H. pylori-negative) and 20 healthy controls confirmed negative by 13C-urea breath test. Blood samples were collected for ELISA analysis of HIF-1α, HIF-2α, and P4H-TM levels. Additionally, lipid profiles were measured and compared among the groups. Results: No significant differences were found among the groups in terms of demographic factors such as age, sex, or body mass index (BMI). However, significant variations were observed in the levels of HIF-1α, HIF-2α, and P4H-TM across all groups (p < 0.001 for each marker). These markers were substantially elevated in the H. pylori-positive gastritis group compared to both the H. pylori-negative and healthy control groups. Receiver Operating Characteristic (ROC) curve analysis revealed that all evaluated markers exhibited strong diagnostic accuracy in differentiating H. pylori-positive individuals from other groups. HIF-1α (AUC: 0.983) and HIF-2α (AUC: 0.981) both achieved 100% sensitivity with specificities of 93.3% and 91.1%, respectively. P4H-TM showed an AUC of 0.927, with 85% sensitivity and 95.6% specificity. Conclusions: These findings indicate that HIF-1α, HIF-2α, and P4H-TM may serve as effective biomarkers for diagnosing H. pylori-positive patients and may be linked to changes in lipid metabolism. The elevated expression of these markers in response to H. pylori infection highlights their potential roles in the inflammatory and hypoxic pathways that contribute to the pathogenesis of gastric diseases such as gastritis.